The Holy Spirit and the physical theories of force field in the W. Pannenberg's systematic theology - Medina Balguerías, Marta (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
In the second volume of his Systematic Theology Wolfhart Pannenberg connects Christian doctrine about the Holy Spirit with Faraday’s understanding of the physical force field and suggests an ontological link between both realities. In this article the main ideas of the Systematic Theology about this issue are presented, an interpretation of their scope according to other texts from the author is given and a balance of this proposal’s contributions and limits is offered.
Keywords: Wolfhart Pannenberg; Systematic Theology; Trinitarian account of creation; Holy Spirit; force field; Theology-Science dialogue; God’s intervention; space-time; angels and demons